Exploring the correlation between translation methods and quality in Mandarin-Indonesian: A case study - Supriyadi, Francisca Akhidnasiwi; Junining, Esti; Yulianto, Wawan Eko (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
This study examines how approaches affect the quality of translating the Mandarin children's narrative "对小虎的称赞" into Indonesian. This study examines how approaches affect translation quality. This study investigates how approaches affect Mandarin-to-Indonesian children's story translation quality, unlike earlier studies. This study uses qualitative research. This study found that the most common method of translating source data into the target language was literal translation. 87.70% of the data underwent literal translation, exhibiting average readability, accuracy, and acceptability. The average readability, correctness, and acceptability of semantic translation, 3.45% of total data, was good. Free translation comprised 49 cases (5.63% of total data) with worse readability, accuracy, and acceptability. We applied communicative translation to 0.92% of the data, which was readable, accurate, and acceptable. Faithful translation had 13 occurrences (1.49% of total data) of illegible, inaccurate, and poor translation. We adapted 0.57% of the data with legible, accurate, and acceptable translations. According to these data, translation method choice strongly impacts translation quality.